OVARIAN AND UTERINE CHANGES INDUCED BY BROMOCRIPTINE INJECTION TO PSEUDOPREGNANT RATS - A.J. Flaih, A.; A. Madhloum, A.; S. Al-Janabi, A. (The Iraqi Journal of Veterinary Medicine, 1988)
Administration of bromocriptine (100 g) to rats on day 7 of pseudopregnancy (P.P.) caused a marked reduction in P.P. length associated with a significant reduction in ovarian weight and an increase in uterine weight. Structural changes included: a marked increase in the percentage of both antral follicles and atretic corpora lutea, endometrial lining height, stromal and myometrial thickness. The results reaffirm prolactin role in maintaining rat luteal function.